Effects of artemether on red blood cell immunity in malaria - LI Xiao-yu; LIANG Hui-zhen (Acta Pharmacologica Sinica, 2016)
Balb/c SPF mice were inoculated with 7.5*10(6) chloroquine-resistant Plasmodium berghei-infected RBC. Their serum circulating immune complex (CIC) increased on d 7 and peaked on d 9. A closely associated depression of serum total complement and C3 to abnormal low levels were found. Mice died soon after. Methyldihydro-artemisinin (artemether), a new antimalarial drug with high activity and low toxicity im 2 mg/kg/d*7 d, maintained normal serum CIC and complement levels, and the time survived. By means of zymosan rosette formation test, C3b receptors on mouse RBC decreased from 22+/-15% to 0.9+/-0.7% in malarial mice, but recovered to 38+/-15% in artemether-treated mice. The erythrocytes of infected mice were very sensitive to low osmosis (0.55% NaCl), low pH (5.4), heat (50 degrees, 30 min) and saponin (0.1 mmol/L) hemolysis. Artemether increased the membrane stability of plasmodia-infected RBC, especially in saponin hemolysis. It is suggested that artemether exerts some modulating effects on RBC immunity other than its schizonts killing effect. Normalized serum C3 level and C3b receptors are favorable in the clearance of pathogenic CIC and malarial antigens.